Old wolf : a fable - Avi, 1937- (Atheneum Books for Young Readers, 2015)
When an old wolf named Nashoba tries to lead his starving pack to food before death sets in--or aggressive newcomer Garby manages to replace him as leader--Nashoba's and his raven friend Merla's lives are irrevocably changed when they encounter 13-year-old Casey, eager to try out his new longbow and demonstrate the skills he's honed on his favorite computer hunting game.